Pyogenic granuloma appearing on port-wine stain: a case report - Askar, Ibrahim; Kilinc, N; Yucetas, A (Acta chirurgiae plasticae (English ed.), 2003)
Background: Pyogenic granuloma has been reported to be associated with hemangiomas and hamartomas, including port-wine stain. It has been suggested that the spontaneous development of pyogenic granuloma in portwine stain might be associated with microscopic arteriovenous anastomoses in highly vascularized areas such as the fingers, hands, lips, tongue and face. Case report: A 25-year-old male patient presented with a history of a reddish, solitary nodule on the posterior cervical area for eight months. There had been an associated port-wine stain at the same localization since birth. Physical examination revealed a solitary, strawberry-like dome-shaped papule, 12 mm in diameter, within a welldemarcated reddish colored surrounding patch which had been present on the posterior cervical area. The lesion was excised, considering pyogenic granuloma arising in a port-wine stain. Histopathologic examination showed a mass of capillaries with variable luminal diameters, infiltration of intlammatory cells, and immature endothelial proliferation in the upper dermis. The capillaries were organized into lobules separated by fibrous stroma and were surrounded by an epithelial collarette. Immunohistochemical staining for factor VIII-related antigen supported all these findings of the port-wine stain. Conclusion: We present a pyogenic granuloma arising in port-wine stain on the posterior cervical area, since the posterior cervical area is not as highly vascular as the fingers, hands, lips, tongue and face. We believed that the collar of the patient’s shirt continuously traumatized port-wine stain, and consequently led to the development of pyogenic granuloma.
Keywords: Hemangioma; Adult; Male; nádory hlavy a krku; biologické markery; hemangiom; lidé; imunohistochemie; pyogenní granulom; dospělí; mužské pohlaví; Head and Neck Neoplasms; Immunohistochemistry; Humans; Biomarkers; Granuloma, Pyogenic